Conserved number of U2 snDNA sites in Piabina argentea, Piabarchus stramineus and two Bryconamericus species (Characidae, Stevardiinae) - Piscor, Diovani [UNESP]; Fernandes, Carlos Alexandre; Parise-Maltempi, Patricia P. [UNESP] (FapUNIFESP (SciELO), 2018)
The chromosomal location of 5S rRNA and U2 snRNA genes of Piabina argentea, Piabarchus stramineus and two Bryconamericus species from two different Brazilian river basins were investigated, in order to contribute to the understanding of evolutionary characteristics of these repetitive DNAs in the subfamily Stevardiinae. The diploid chromosome number was 2n = 52 for Bryconamericus cf. iheringii, Bryconamericus turiuba, Piabarchus stramineus and Piabina argentea. The 5S rDNA clusters were located on one chromosome pair in P. stramineus and B. cf. iheringii, and on two pairs in B. turiuba and P. argentea. The U2 snDNA clusters were located on the one pair in all species. Two-color FISH experiments showed that the co-localization between 5S rDNA and U2 snDNA in P. stramineus can represent a marker for this species. Thus, the present study demonstrated that the number of U2 snDNA clusters observed for the four species was conserved, but particular characteristics can be found in the genome of each species.
Keywords: 5S rDNA; Chromosome; Diploid number; Repetitive DNA; Splicing